Identifikasi Akuifer Air Tanah Di Kaki Gunung Api Gamalama Pulau Ternate Menggunakan Data Geolistrik Tahanan Jenis 2-Dimensi - Parnadi, Wahyudi W.; Salam, Ramdani (JFT: Jurnal Fisika dan Terapannya, 2022)
This study aimed to identify the distribution of groundwater aquifers and seawater intrusion at the foot of Mount Gamalama on Ternate Island using 2-dimensional electrical resistivity data. This island has experienced significant eruptions that have caused new deposits to form on its body and have caused the formation of an aquifer layer. Small in size but surrounded by seawater, Ternate Island experiences seawater intrusion at the aquifer zones. We researched using 2-dimensional electrical resistivity techniques on nine lines in the eastern and southern parts of the Island, namely the Bandara, FKIP, PDAM, Kayu Merah, Skep, Lapangan Fitu, Sasa, and Takome lines. Each line has a length of 75 meters to 230 meters. This measurement was carried out in the direction parallel to the shoreline using two electrode configurations: the Wenner and the Wenner-Schlumberger. Electrode spacing was 10m. The results showed that aquifer zones with a resistivity value of 10 – 150 Ohm.m exist in the eastern and southern parts of the island. We found seawater intrusion in the eastern part of the island on the PDAM lines with a resistivity value of 1 – 10 Ohm.m. The zones show high conductance values in the low resistivity range of 3.01 to 3.41 Ohms. Visual evidence reveals that this PDAM line locates at the beach, where Ternate inhabitants utilize groundwater excessively through dug wells.